RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS AND WORK CLIMATE WITH HYDRATION STATUS OF WORKERS IN PT X INDUSTRY - Eka Novia Nur Anggraeni; Ratih Damayanti; Herman Bagus Dwicahyo (Journal of Vocational Health Studies, 2026)
Background: Working in hot climates can also lead to health problems such as dehydration. Dehydration is the excessive loss of fluid from body tissues. Dehydration can be caused by fluid loss and bleeding. Dehydration can also occur due to increased fluid requirements, such as fever, high environmental temperatures, and extreme activity. Purpose: This study aims to analyze the relationship between individual characteristics and work climate with hydration status in workers in the production department of PT X. Method: This study used a cross-sectional design, with analytical observation methods, and a sample size of 57 workers in the production department. The relationship between the research variables was examined using the contingency coefficient statistical test. Result: The results of the study showed that there was a significant correlation between hydration status and age (p value = 0.003), Body Mass Index (BMI) (p value = 0.038), drinking water intake (p value = 0.000), and work climate conditions (p value = 0.020). Conclusion: This study indicates that some production workers are not well hydrated. This is based on the analysis of four variables: age, body mass index, water consumption, and work environment. These variables were found to have a significant correlation with workers' hydration status, with the strength of the relationship ranging from moderate to strong.